2017
DOI: 10.1371/journal.pntd.0005679
|View full text |Cite
|
Sign up to set email alerts
|

Development of ELISAs for diagnosis of acute typhoid fever in Nigerian children

Abstract: Improved serodiagnostic tests for typhoid fever (TF) are needed for surveillance, to facilitate patient management, curb antibiotic resistance, and inform public health programs. To address this need, IgA, IgM and IgG ELISAs using Salmonella enterica serovar Typhi (S. Typhi) lipopolysaccharide (LPS) and hemolysin E (t1477) protein were conducted on 86 Nigerian pediatric TF and 29 non-typhoidal Salmonella (NTS) cases, 178 culture-negative febrile cases, 28 “other” (i.e., non-Salmonella) pediatric infections, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 60 publications
(72 reference statements)
1
17
0
Order By: Relevance
“…For example, a recent study has shown that IgA and IgM against S . Typhi lipopolysaccharide may be a specific marker of acute typhoid infection and is a promising target for diagnostic test development 25…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study has shown that IgA and IgM against S . Typhi lipopolysaccharide may be a specific marker of acute typhoid infection and is a promising target for diagnostic test development 25…”
Section: Introductionmentioning
confidence: 99%
“…We have previously identified HlyE in high-throughput immunoscreens as an antigen that correctly identified individuals with acute typhoid or paratyphoid fever in Dhaka, Bangladesh, using plasma and antibody-in-lymphocyte supernatant, a surrogate marker of the mucosal immune response, and this finding has been confirmed by other groups [28,29,33]. HlyE is a pore-forming toxin that affects bacterial growth within human macrophages and contributes to the cytotoxicity and invasion of epithelial cells [17][18][19].…”
Section: Discussionmentioning
confidence: 73%
“…In a study in which human challenge participants in the United Kingdom were used as a training cohort and typhoid cases and febrile controls from Nepal were used for validation, IgA responses to LPS had the highest diagnostic accuracy (AUC, 0.88) for a single antigen-antibody isotype, but HlyE was also selected for accuracy in several models [28]. In a study in Nigeria, LPS IgA, IgM and IgG responses (AUCs, 0.90-0.93) and HlyE IgG responses (AUC, 0.91) performed well in distinguishing typhoid from other infections [29]. In our current analysis in South Asia, we found that HlyE IgA (AUC 0.93) performed better than LPS IgA (AUC, 0.92) or MP IgA (AUC, 0.83).…”
Section: Discussionmentioning
confidence: 99%
“…The candidates for the ELISAs in the Nigerian setting was based on a proteome microarray data previously carried out by the same research group where they identified hemolysin E and LPS as putative biomarker targets. The receiver operator characteristic area under the curve (ROC-AUC) values suggested that LPS-specific IgA and IgA+M ELISA, in particular, was sensitive in diagnosing acute typhoid, and could discriminate well between typhoid and healthy, and other febrile bacteremias commonly encountered in Nigeria [ 62 , 63 ]. In another study in Bangladesh, 12 proteins were expressed and purified to design ELISAs and tested in a cohort of febrile patients.…”
Section: Serologic Testingmentioning
confidence: 99%